Middle Judaism Jewish thought,300 B.C.E.-200 C.E. - Boccaccini, Gabriele, 1958- (Minneapolisn MN Fortress, 1991)
Includes bibliographical references and indexes.
Keywords: Judaism -- history -- post-exilic period, 586 B.C.-210 A.D.